Dynamic properties of the alkaline vesicle population at hippocampal synapses - Röther, Mareike; Brauner, Jan M.; Ebert, Katrin; Welzel, Oliver; Jung, Jasmin; Bauereiß, Anna; Kornhuber, Johannes; Groemer, Teja W. (PLoS ONE, 2014)
In compensatory endocytosis, scission of vesicles from the plasma membrane to the cytoplasm is a prerequisite for intravesicular reacidification and accumulation of neurotransmitter molecules. Here, we provide time-resolved measurements of the dynamics of the alkaline vesicle population which appears upon endocytic retrieval. Using fast perfusion pH-cycling in live-cell microscopy, synapto-pHluorin expressing rat hippocampal neurons were electrically stimulated. We found that the relative size of the alkaline vesicle population depended significantly on the electrical stimulus size: With increasing number of action potentials the relative size of the alkaline vesicle population expanded. In contrast to that, increasing the stimulus frequency reduced the relative size of the population of alkaline vesicles. Measurement of the time constant for reacification and calculation of the time constant for endocytosis revealed that both time constants were variable with regard to the stimulus condition. Furthermore, we show that the dynamics of the alkaline vesicle population can be predicted by a simple mathematical model. In conclusion, here a novel methodical approach to analyze dynamic properties of alkaline vesicles is presented and validated as a convenient method for the detection of intracellular events. Using this method we show that the population of alkaline vesicles is highly dynamic and depends both on stimulus strength and frequency. Our results implicate that determination of the alkaline vesicle population size may provide new insights into the kinetics of endocytic retrieval.
EVALuna2:23664

Electroconvulsive Therapy Hasn't Negative Effects on Short-Term Memory Function, as Assessed Using a Bedside Hand-Held Device - Mueller, Helge H. O.; Reike, Mareen; Grosse-Holz, Simon; Röther, Mareike; Likke, Caroline; Philipsen, Alexandra; Kornhuber, Johannes; Groemer, Teja W. (Mental Illness, 2017)
Electroconvulsive therapy (ECT) is effective in the treatment of treatment-resistant major depression. The fear of cognitive impairment after ECT often deters patients from choosing this treatment option. There is little reliable information regarding the effects of ECT on overall cognitive performance, while short-term memory deficits are well known but not easy to measure within clinical routines. In this pilot study, we examined ECT recipients' pre- and post-treatment performances on a digital ascending number tapping test. We found that cognitive performance measures exhibited good reproducibility in individual patients and that ECT did not significantly alter cognitive performance up to 2 hours after this therapy was applied. Our results can help patients and physicians make decisions regarding the administration of ECT. Digital measurements are recommended, especially when screening for the most common side effects on cognitive performance and short-term memory.
EVALuna2:33739

Erratum to: The Antidepressant Fluoxetine Mobilizes Vesicles to the Recycling Pool of Rat Hippocampal Synapses During High Activity - Jung, Jasmin; Loy, Kristina; Schilling, Eva-Maria; Röther, Mareike; Brauner, Jan M.; Huth, Tobias; Schlötzer-Schrehardt, Ursula; Alzheimer, Christian; Kornhuber, Johannes; Welzel, Oliver; Groemer, Teja W. (Molecular Neurobiology, 2017)
EVALuna2:21331

The androgen model of suicide completion - Lenz, Bernd; Röther, Mareike; Bouna-Pyrrou, Polyxeni; Mühle, Christiane; Tektas, Ozan Y.; Kornhuber, Johannes (Progress in Neurobiology, 2019)
Suicide is a devastating public health issue that imposes severe psychological, social, and economic burdens not only for the individuals but also for their relatives, friends, clinicians, and the general public. Among the different suicidal behaviors, suicide completion is the worst and the most relevant outcome. The knowledge of biological etiopathological mechanisms involved in suicide completion is limited. Hitherto, no objective markers, either alone or in combination, can reliably predict who will complete a suicide. However, such parameters are strongly needed to establish and optimize prediction and prevention. We introduce here a novel ideation-to-completion framework in suicide research and discuss the problems of studies aiming at identifying and validating clinically useful markers. The male gender is a specific risk factor for suicide, which suggests that androgen effects are implicated in the transition from suicidal ideation to suicide completion. We present multiple lines of direct and indirect evidence showing that both an increased prenatal androgen load (with subsequent permanent neuroadaptations) and increased adult androgen activity are involved in suicide completion. We also review data arguing that modifiable maternal behavioral traits during pregnancy contribute to the offspring's prenatal androgen load and increase the risk for suicide completion later in life. We conclude that in utero androgen exposure and adult androgen levels facilitate suicide completion in an synergistic manner. The androgen model of suicide completion provides the basis for the development of novel predictive and preventive strategies in the future.
EVALuna2:211632

The antidepressant fluoxetine mobilizes vesicles to the recycling pool of rat hippocampal synapses during high activity - Jung, Jasmin; Loy, Kristina; Schilling, Eva-Maria; Röther, Mareike; Brauner, Jan M.; Huth, Tobias; Schlötzer-Schrehardt, Ursula; Alzheimer, Christian; Kornhuber, Johannes; Welzel, Oliver; Groemer, Teja W. (Molecular Neurobiology, 2014)
Effects of the antidepressant fluoxetine in therapeutic concentration on stimulation-dependent synaptic vesicle recycling were examined in cultured rat hippocampal neurons using fluorescence microscopy. Short-term administration of fluoxetine neither inhibited exocytosis nor endocytosis of RRP vesicular membranes. On the contrary, acute application of the drug markedly increased the size of the recycling pool of hippocampal synapses. This increase in recycling pool size was corroborated using the styryl dye FM 1-43, antibody staining with ?Syt1-CypHer(TM)5E and overexpression of synapto-pHluorin, and was accompanied by an increase in the frequency of miniature postsynaptic currents. Analysis of axonal transport and fluorescence recovery after photobleaching excluded vesicles originating from the synapse-spanning superpool as a source, indicating that these new release-competent vesicles derived from the resting pool. Super resolution microscopy and ultrastructural analysis by electron microscopy revealed that short-term incubation with fluoxetine had no influence on the number of active synapses and synaptic morphology compared to controls. These observations support the idea that therapeutic concentrations of fluoxetine enhance the recycling vesicle pool size and thus the recovery of neurotransmission from exhausting stimuli. The change in the recycling pool size is consistent with the plasticity hypothesis of the pathogenesis of major depressive disorder as stabilization of the vesicle recycling might be responsible for neural outgrowth and plasticity.
EVALuna2:2369